The Biological Effect of Extremely Low Frequency Electromagnetic Fields and Vibrations on Barley Seed Hydration and Germination - Armine Amyan; Sinerik Ayrapetyan (The Scientific World Journal)
The changes of wet and dry weights and germination of barley seed in different periods of its swelling in nontreated (control), extremely low frequency electromagnetic fields (ELF EMF) )treated, and extremely low frequency vibrations (ELFV)treated cold (4°C) and warm (20°C) distilled water (DW) were studied. The metabolic-dependent seed hydration, dry weight dissolving, germination, and water binding in seed were modulated by preliminary EMF- and ELFV-treated DW. Frequency “windows” for the effect of EMF and ELFV on seed hydration, solubility, water binding in seed, and germination were discovered. These “windows” were different for EMF and ELFV, as well as in various phases of seed swelling. It is suggested that EMF-induced water structure modification has a different biological effect on the process of seed hydration, solubility, water binding in seed, and germination compared to ELFV.